Optimum Design of Corona Ring of Composite Insulators Considering the Effect of Mutual Phases by Monte Carlo and Coordinate Search Intelligente Algorithms - Mostafa Khajavi; Sajad Bagheri; Asaad Shemshadi (مجله مدل سازی در مهندسی)
Today, composite insulators are used in high-voltage power transmission lines, especially in polluted and humid areas. One of the parameters affecting the aging of composite insulators is the control of the Electric Field Intensity (EFI) distribution on the creepage distance of the insulator. Designing corona ring is considered as one of the important factors in reducing EFI. In this paper, the changes in the EFI on the creepage distance of the 230 kV composite insulator have been investigated and calculated with and without considering the effects of the corona ring, tower structure, conductor, hardware, and mutual phases using the Finite Element Method (FEM) and in three dimensions in software COMSOL. Then, the appropriate objective function was defined to minimize the maximum EFI on the creepage distance of the composite insulator. Finally, Monte Carlo and coordinate search algorithms were used for the optimum design of the corona ring parameters of the composite insulator, including the diameter, thickness, and Installation position of the corona ring in the high voltage potential part, and compared with other non-gradient-based methods. The simulation results showed that the design and calculation of the optimal parameters of the corona ring using Monte Carlo and coordinate search algorithms reduced the maximum EFI on the creepage distance of the composite insulator by 78% compared to the case without the corona ring, which is the innovation of this paper to other published works..